Agmatine augmentation in treatment-resistant obsessive-compulsive disorder: a prospective open-label case series - Salvi, Joshua D. (Frontiers in Psychiatry, 2026)
ImportanceObsessive-compulsive disorder (OCD) remains treatment-resistant in 40-60% of patients despite adequate trials of serotonin reuptake inhibitors and cognitive behavioral therapy. Glutamatergic dysfunction in cortico-striato-thalamo-cortical circuits has emerged as a key pathophysiologic mechanism, prompting investigation of glutamatergic modulators as augmentation strategies.ObjectiveTo evaluate the safety, tolerability, and preliminary efficacy of agmatine sulfate augmentation in treatment-resistant OCD.DesignProspective open-label case series conducted between May 2025 and November 2025.SettingOutpatient psychiatry practice.ParticipantsFive adults (ages 28–54 years) with treatment-resistant OCD who had failed multiple serotonin reuptake inhibitor trials and at least one augmentation strategy.InterventionAll patients were treated with agmatine sulfate initiated at 650 mg daily, increased to 1300 mg daily after one week, as augmentation to stable doses of selective serotonin reuptake inhibitors.Main outcomes and measuresWe measured the OCD severity using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) scores assessed at baseline and multiple time points over 112 days. Primary outcome was change in Y-BOCS score from baseline.ResultsExponential decay modeling revealed gradual symptom reduction with half-life of 16.4 days. Two of five patients (40%) demonstrated clinically meaningful improvement (≥25% Y-BOCS reduction). Agmatine was well-tolerated with no discontinuations due to adverse effects. Mild transient gastrointestinal symptoms occurred in two patients.Conclusions and relevanceThis case series provides preliminary, early evidence supporting agmatine’s safety and potential efficacy as augmentation therapy in treatment-resistant OCD. The gradual response pattern and 40% responder rate warrant controlled trials to definitively establish efficacy and identify predictors of treatment response.